Examining the impact of agile leadership on work commitment: Mediating role of organizational culture - Mohammad Adam Husein; M Noor Salim; Mafizatun Nurhayati; Setyo Riyanto (Journal of Enterprise and Development (JED), 2023)
Purpose — This research aims to investigate the influence of agile leadership in Islamic schools  on work commitment, using organizational culture as a mediator.Method — This research employed quantitative causality methods. The study's population comprised all 31 teachers from Azhari Islamic School Rasuna, all of whom were included as samples. The data analysis utilized Structural Equation Model-Partial Least Square (SEM-PLS).Result — The research findings demonstrate a positive influence of agile leadership on organizational culture. However, agile leadership does not significantly affect teacher work commitment, and organizational culture does not mediate the influence of agile leadership on teacher work commitment.Contribution — This research contributes to the existing literature by addressing a gap in previous research, which had not examined the influence of agile leadership on work commitment.